2018
DOI: 10.1136/bmjopen-2017-019453
|View full text |Cite
|
Sign up to set email alerts
|

Is body mass index associated with symptom severity and health-related quality of life in irritable bowel syndrome? A cross-sectional study

Abstract: ObjectiveThe aim of this study was to describe the body mass index (BMI) distribution in patients with irritable bowel syndrome (IBS) based on the Rome III criteria and to evaluate the association of BMI with symptom severity and quality of life (QOL).MethodsA cross-sectional study was carried out in patients visiting our outpatient functional gastrointestinal disorders specialty clinic. IBS diagnosis was made based on Rome III criteria. IBS symptom severity was investigated using the IBS severity score system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(27 reference statements)
1
6
1
1
Order By: Relevance
“…A survey carried out in an outpatient setting in Germany between 2011 and 2016 showed that 59.0% of patients with IBS were in the normal weight range, 30.3% were overweight or obese, and 10.7% were underweight. 32 The proportion of obese linaclotide users in the United Kingdom and in Spain is consistent with the figures reported in Germany. Obese patients who potentially used linaclotide to help with weight loss could not be distinguished in our study from obese patients who used linaclotide to treat IBS-C.…”
Section: Discussionsupporting
confidence: 83%
“…A survey carried out in an outpatient setting in Germany between 2011 and 2016 showed that 59.0% of patients with IBS were in the normal weight range, 30.3% were overweight or obese, and 10.7% were underweight. 32 The proportion of obese linaclotide users in the United Kingdom and in Spain is consistent with the figures reported in Germany. Obese patients who potentially used linaclotide to help with weight loss could not be distinguished in our study from obese patients who used linaclotide to treat IBS-C.…”
Section: Discussionsupporting
confidence: 83%
“…This rate was much lower in the British study, where it was around 6%. (10) A quarter of our patients had a history of visceral and/or gynecological surgery. The association between IBS and a history of surgery was demonstrated in a study by the American Gastroenterological Association in 2004, which found that IBS was associated with a 3-fold increased risk of cholecystectomy, appendectomy and hysterectomy (11).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of IBS on quality of life has been examined in various studies; gender 26 , age 27 , anxiety level 28,29 , depression level 26 , BMI 30,31 have all been evaluated. In contrast to our study, Tang et al 32 found that women with IBS had lower IBS-QOL scores (74.09 ± 8.06) than men (80.40 ± 6.62).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies, in our study, no significant correlation was found between IBS-QOL scores and PSS-14 scores. Being overweight is a common phenomenon in patients with IBS 30 . The association between QOL and symptom severity followed a negative dose-response pattern.…”
Section: Discussionmentioning
confidence: 99%